Destination love in Asia: Understanding the role of experiences and perceived value in building tourist loyalty - Wahyudi, Lilik; Hariningsih, Endang (Asian Management and Business Review, 2026)
This study proposes an integrated model to investigate how destination experience, destination love, and perceived value drive tourist loyalty, underpinned by attachment theory and expectancy-value theory. Addressing gaps in previous loyalty research, it combines emotional and cognitive constructs that have often been examined in isolation. Based on survey data from 642 respondents and analyzed using PLS-SEM with SEMinR, the findings reveal that destination experience significantly enhances destination love, perceived value, and loyalty. Moreover, destination love and perceived value act as mediators, strengthening the formation of loyalty. The model shows moderate explanatory power, validating the theoretical integration. This study contributes novel insights by unifying emotional attachment and value perceptions within a single framework, offering a more comprehensive understanding of loyalty-building mechanisms. Practically, the findings underscore the importance of delivering emotionally engaging and value-rich experiences to foster tourist loyalty and enhance destination competitiveness. The results extend existing theories and provide a strong foundation for future research in cross-cultural and emerging market contexts.